2018
DOI: 10.1002/prca.201800062
|View full text |Cite
|
Sign up to set email alerts
|

Direct Monitoring of Fucosylated Glycopeptides of Alpha‐Fetoprotein in Human Serum for Early Hepatocellular Carcinoma by Liquid Chromatography–Tandem Mass Spectrometry with Immunoprecipitation

Abstract: These findings suggest that glycopeptide-based LC-MS/MS is a promising method and that AFP-fuc% is a clinically useful parameter for differentiating between early HCC and liver cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 35 publications
1
40
0
Order By: Relevance
“…Most recently, An and coworkers (Kim et al, ) developed a quantitative LC‐MS/MS‐PRM to monitor fucosylated glycopeptides in serum AFP to distinguish between HCC and cirrhosis patients. Because AFP is normally present at low levels in serum, even in patients with liver disease, a more sensitive approach is required.…”
Section: Verification Lc‐mrm Analysis Of Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, An and coworkers (Kim et al, ) developed a quantitative LC‐MS/MS‐PRM to monitor fucosylated glycopeptides in serum AFP to distinguish between HCC and cirrhosis patients. Because AFP is normally present at low levels in serum, even in patients with liver disease, a more sensitive approach is required.…”
Section: Verification Lc‐mrm Analysis Of Glycosylationmentioning
confidence: 99%
“…With a combination of these approaches, the MS detection limit was significantly improved (LOD < 2 ng/mL). The result showed that the relative percentage of fucosylated AFP (AFP‐fuc%) had a better performance than serum AFP levels to differentiate early‐HCC and cirrhosis (AUC = 0.962) with a sensitivity of 92.3% (Kim et al, ).…”
Section: Verification Lc‐mrm Analysis Of Glycosylationmentioning
confidence: 99%
“…First, we selected target glycopeptides that are predominant in HCC patients, for determining the relative percent of fucosylation as in our previous report [13]. The target glycopeptides for LC‐PRM MS analysis are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…All samples were prepared as described in our previous report [13]. Briefly, 63 μL (6.3 mg) of resuspended tosyl‐activated Dynabeads MyOne magnetic beads was washed by a coating buffer (0.1 M sodium borate, pH 9.5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation